2012
DOI: 10.1016/j.pbb.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine improves response inhibition in alcohol dependent patients: A placebo-controlled pilot study

Abstract: Rationale Quetiapine has been shown to be a promising medication for the treatment of alcoholism. As an atypical antipsychotic medication with antagonist activity at D1 and D2, 5-HT1A and 5-HT2A, H1 and α1 and α2 receptors, quetiapine has been found to decrease impulsivity in other psychiatric disorders but its effects on impulsivity have not been studied in alcohol dependent patients. Objective This study seeks to test the effects of quetiapine on a specific dimension of impulsivity, namely response inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Given the potential difficulty that occurs between differentiating delirium related to alcohol withdrawal to that of ICU or hospital stay, it is difficult to understand their place in therapy. Atypical antipsychotics have been evaluated in the reduction of alcohol use in alcohol-dependent patients with contrasting results but have not been studied in acute alcohol withdrawal [34][35][36]. Given the potential adverse effects that may occur with antipsychotic use, including neuroleptic malignant syndrome and QTc interval prolongation, and variable efficacy and safety, the low incidence of antipsychotic use in our population may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential difficulty that occurs between differentiating delirium related to alcohol withdrawal to that of ICU or hospital stay, it is difficult to understand their place in therapy. Atypical antipsychotics have been evaluated in the reduction of alcohol use in alcohol-dependent patients with contrasting results but have not been studied in acute alcohol withdrawal [34][35][36]. Given the potential adverse effects that may occur with antipsychotic use, including neuroleptic malignant syndrome and QTc interval prolongation, and variable efficacy and safety, the low incidence of antipsychotic use in our population may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical antipsychotics (which transiently block D2 receptors) have looked promising in the past, as evidenced by combined work showing that quetiapine improves response inhibition in AUD patients (Moallem and Ray, 2012), and appears to decrease drinking in type B alcoholics (Kampman et al, 2007) in a larger, multisite study. However, typology did not predict response to quetiapine in a second study attempting to replicate the findings from Kampmen et al (Litten et al, 2013), and therefore studies within this drug class may not be highest on the priority list in future mediational studies focused on cognitive control.…”
Section: Clinical Significance Of Deficits In Cognitive Controlmentioning
confidence: 99%
“…The results of this study showed quetiapine improved sleep disturbance and may help in alcohol reduction and maintaining abstinence. Moallem et al 4 adds further evidence with their published pilot study showing that quetiapine improves response inhibition in alcohol dependence. Sattar et al 5 also showed the benefits of quetiapine in the treatment of substance dependence disorders.…”
Section: Discussionmentioning
confidence: 90%